The cultural approach to development and cultural rights as a proposal for the resizing of collective reparation (2020)
To give superficial importance to the cultural aspect in the context of collective reparation, particularly to the effects caused in this area to groups and communities of victims, can have serious repercussions on the comprehensiveness of reparation and its transformative effect. In this sense, a reflection on collective reparation that takes as an essential postulate the inclusion of the cultural aspect in the process is necessary, which constitutes the main objective of this work. For this purpose, the theoretical notes of the cultural approach to development and other approaches that nurture it are methodologically picked up as key elements towards a resizing of collective reparation. Finally, this reparation allows enhancing their transformative claim and opens the door to local and community development processes to make possible both the agency of their rights as victims, as well as their rights as individuals and citizens